Toxicity of hydroquinone to different freshwater phototrophs is influenced by time of exposure and pH - Bährs, Hanno; Putschew, Anke; Steinberg, Christian E. W. (Environmental science and pollution research international, 2013)
The interaction of natural organic matter with phytoplankton communities in freshwater ecosystems is an intensively studied subject matter. Previous studies showed that apparently plant-derived phenols were able to inhibit algal and cyanobacterial growth. Furthermore, it was also assumed that humic substances (HS), which comprise the major part of dissolved organic carbon in freshwater ecosystems, directly interact with freshwater phototrophs. For example, quinoid building blocks of HS were thought to be algicidal. To identify key environmental variable for the toxic action of potential quinone algicides, we tested the toxicity of hydroquinone (HQ) to different eukaryotic and prokaryotic freshwater phototrophs in terms of growth performance and investigated also the effect of HQ oxidation at different pH values on its algicidal potential. It was shown that cyanobacterial species were much more susceptible to hydroquinone than coccal green algal species were, with Microcystis aeruginosa being the most sensitive species by far. In addition, it was obvious that the aging of hydroquinone-stock solution at pH 11 led to polymerization and, by this process, to a total loss of toxicity; whereas the algicidal potential sustained if the polyphenol was kept at pH 7. Since most lakes with heavy blooms of phototrophs possess pH values clearly above 7.0, it is questionable, if polyphenols in general and quinones in particular are the effective chemicals and if litter and straw leachates are applied as means to combat algal and cyanobacterial blooms.